Aeroelastic stability of two long-span arch structures: A collaborative experience in two wind tunnel facilities. (15th July 2016) - Mannini, Claudio; Belloli, Marco; Marra, Antonino M.; Bayati, Ilmas; Giappino, Stefano; Robustelli, Fabio; Bartoli, Gianni
Graphical abstract: Highlights: The stability of two long-span arch structures was studied in two wind tunnels. Good agreement between the results of sectional and full-aeroelastic model tests. The structures exhibited a galloping-type instability at low reduced wind speed. Interference of VIV and galloping for the rectangular 3:2 cross section. Eurocode 1 provides non-conservative prescriptions for this type of problem. Abstract: In this paper, a rare example of comparison between sectional and full-aeroelastic model tests is presented. Interestingly, the experiments were conducted in two very different wind tunnel facilities by different research teams. The study concerns two long-span steel arch structures recently built in Milan, Italy, for Expo 2015 World Fair. The structures have only aesthetic purposes and are therefore very flexible and light, which makes them sensitive to wind-induced excitation and prone to aeroelastic instabilities. In particular, in smooth flow an interesting phenomenon of interference between vortex-induced vibration and galloping was observed up to high values of the Scruton number. This aeroelastic instability is very dangerous as large-amplitude vibrations can occur in wind speed ranges where they are not expected, at least for what classical theories for vortex-induced vibration and quasi-steady galloping are concerned. Moreover, the provisions of Eurocode 1 resulted clearly unsuitable and non-conservative to address such a phenomenon. Despite the differences in the facilities and in the models, a good agreement was found between the results obtained in the two laboratories. The major discrepancies were observed in the transitional behavior for intermediate values of the Scruton number, the sectional model showing a more unstable behavior. The tests on the full-aeroelastic model also allowed considering the effect of the angle of wind exposure of the structures, both the in-plane and the out-of-plane vibrations of the arches and the dynamic response to turbulent wind. In particular, a set of tests in smooth flow was performed accounting for the presence of the other arch and of the surrounding buildings. A particular dynamic excitation of the in-plane flexural modes of the structures was observed in well defined ranges of flow speeds when one arch is in the wake of the other. Finally, both experimental campaigns highlighted the need for the installation of tuned mass dampers on the real structures to guarantee their safety. The effectiveness of these devices against the observed galloping-type instability was also verified through wind tunnel tests on the full-aeroelastic model.